2021
DOI: 10.1038/s41598-021-85085-w
|View full text |Cite
|
Sign up to set email alerts
|

First isolation and analysis of caesium-bearing microparticles from marine samples in the Pacific coastal area near Fukushima Prefecture

Abstract: A part of the radiocaesium from the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident was emitted as glassy, water-resistant caesium-bearing microparticles (CsMPs). Here, we isolated and investigated seven CsMPs from marine particulate matter and sediment. From the elemental composition, the 134Cs/137Cs activity ratio, and the 137Cs activity per unit volume results, we inferred that the five CsMPs collected from particulate matter were emitted from Unit 2 of the FDNPP, whereas the two CsMPs collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…An approximately 1-mm 2 area surrounding high-radioactivity spots of the Kapton tape was cut. According to previous studies (Higaki et al 2017;Kurihara et al 2020;Miura et al 2018Miura et al , 2021, high spots indicate the presence of CsMPs. If high-radioactivity spots remained on the non-woven fabric fragment, the fragment was treated again by ultrasonication.…”
Section: Isolation and Measurement Of Radioactivity Of Cesium-bearing...mentioning
confidence: 76%
“…An approximately 1-mm 2 area surrounding high-radioactivity spots of the Kapton tape was cut. According to previous studies (Higaki et al 2017;Kurihara et al 2020;Miura et al 2018Miura et al , 2021, high spots indicate the presence of CsMPs. If high-radioactivity spots remained on the non-woven fabric fragment, the fragment was treated again by ultrasonication.…”
Section: Isolation and Measurement Of Radioactivity Of Cesium-bearing...mentioning
confidence: 76%
“…Moreover, CsMPs can be transported (e.g., as dust in the air, by flowing water, etc. ), resulting in an unpredictable, changing radio-Cs distribution in the environment. Given the existence of CsMPs and their potential long-term impact on the environment and human health, it is essential to detect, evaluate, and differentiate the varying forms of radio-Cs (micro-particle or bulk) found in samples.…”
Section: Introductionmentioning
confidence: 99%
“…The total radioactivity of other bulk samples was larger in periphyton (17-220 Bq), CPOM (47-285 Bq), and SS (3-54 Bq) than that of caddisfly due to the larger sample weight for periphyton and CPOM samples, and the higher 137 Cs activity concentration in SS samples, resulting in a small CsMP radioactivity fraction and a small effect of CsMPs on 137 Cs activity concentration. Thus, it should be noted that the inclusion of CsMPs could substantially increase the measured value of 137 Cs activity concentration, especially for samples with low total radioactivity, such as small insects or plankton samples [10].…”
Section: Radioactivity Fraction Of Csmpsmentioning
confidence: 99%
“…The total RCs deposited on land is 3-6 PBq [8], but the ratio of RCs abundance in CsMPs to water-soluble RCs is unknown. CsMPs are important for understanding and predicting the fate of RCs in the environment and their uptake by organisms [9,10]. After CsMPs were first reported by Adachi et al [11], subsequent studies revealed two types of CsMPs: Type A and Type B particles [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation